Implementation of Corporate Social Responsibility Program PT. Allegrindo and Their Benefits for The Social Economic Life of The Community Around Nagori Urung Panei, Purba District, Simalungun Regency - Hutajulu, Anggiat Hutajulu (Journal of Sumatera Sociological Indicators, 2022)
Corporate Social Responsibility is an activity carried out by a company as a form of concern and responsibility for the surrounding community. The purpose of this study was to determine the form of PT Allegrindo's CSR program and its benefits for the socio-economic life of the surrounding community. This type of research is a qualitative research using descriptive methods. The data collection technique was carried out by means of observation, in-depth interviews, and literature study. The results showed that PT Allegrindo's CSR program is still in the form of a caricative (Charity). This program is a form of the company's response to responding to demands from the surrounding community. The program is contained in the fields of education, agriculture, and socio-religion. It is undeniable that the company's CSR program can provide benefits for the current socio-economic life of the surrounding community. However, PT Allegrindo's CSR program has not been able to provide long-term benefits for the socio-economic life of the surrounding community. Companies in general, and PT Allegrindo in particular are expected to be able to implement community empowerment-based CSR programs so that they can provide benefits to the surrounding community in the long term.